Political literacy in composition and rhetoric : defending academic discourse against postmodern pluralism - Lazere, Donald (Southern Illinois University Press, 2015)
"A critique of the postmodern pluralist faction in composition and rhetoric that has led these disciplines to value diverse student voices over the teaching of critical thinking and writing, this book explains why political literacy is necessary and how instructors may teach it"--